PENGARUH PEMBERIAN SARI KURMA TERHADAP KEMAMPUAN DAYA TAHAN TIM SEPAKBOLA SMAN 1 BANUHAMPU KABUPATEN AGAM - Rizkia Rahmat; Wilda Welis (JURUSAN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2018)
The problem of this research is the low endurance ability of the Banuhampu SMA N 1 soccer team player in Banuhampu Subdistrict, Agam Regency. This study aims to determine the effect of date palm extract on the endurance ability of the football team players of SMA N 1 Banuhampu, Banuhampu District, Agam Regency. The type of this research is quasi-experimental, the population in this study were all football team players of SMA N 1 Banuhampu, Banuhampu Subdistrict, Agam Regency, which numbered 20 people. The sampling technique is total sampling, which is to take the entire population to become a sample of as many as 20 people. Data collection was carried out by pre-test and post-test the endurance ability of the SMA N 1 Banuhampu football team in Banuhampu Subdistrict Agam Regency using the bleep test (Multi Stage Fines Test). Comparative analysis using a different mean test formula (t test) with a significance level of α 0.05. From the analysis of the data obtained the results: The effect of giving palm juice to the endurance ability of football team players Banuhampu N 1 High School Banuhampu District Agam, with the acquisition of the test coefficient